Cryptotanshinone affects HFL-1 cells proliferation by inhibiting cytokines secretion in RAW264.7 cells and ameliorates inflammation and fibrosis in newborn rats with hyperoxia induced lung injury - Ma, Mengmeng; Bao, Tianping; Li, Jingyan; Cao, Linxia; Yu, Bingrui; Hu, Jingjing; Cheng, Huaiping; Tian, Zhaofang (Frontiers in Pharmacology, 2023)
Bronchopulmonary dysplasia (BPD) is a common complication of prematurity and has no specific treatment option. Moreover, inflammation and fibrosis play a vital role in the development of BPD. Thus, this study aimed to explore the role of the anti-inflammatory and anti-fibrotic drug cryptotanshinone (CTS) in the treatment of inflammation and fibrosis in BPD. In vivo, Sprague-Dawley rats (male) were divided into air, hyperoxia and CTS groups with different dose interventions (7.5, 15, 30 mg/kg). A BPD rat model was induced by continuous inhalation of hyperoxia (95%) for seven days, during which different doses of CTS were injected intraperitoneally. Furthermore, histological examination, hydroxyproline content measurement, western blot and real-time quantitative polymerase chain reaction were used to detect the levels of inflammation and fibrosis in the tissues. RAW264.7 cells exposed to 95% oxygen were collected and co-cultured with fibroblasts to determine the expression levels of α-SMA, collagen-Ⅰ and MMPs. The levels of pro-inflammatory cytokines such as TNF-α, IL-6 and pro-fibrotic factor TGF-β1 in the supernatants were measured using enzyme-linked immunosorbent assay. Haematoxylin and eosin staining revealed that CTS reduced the inflammatory response in rat lungs. Masson staining revealed that CTS alleviated the level of pulmonary fibrosis. CTS also reduced the levels of TNF-α, IL-6 and TGF-β1 along with the expression of the fibrosis marker α-SMA in lung tissue. Similarly, in vitro analysis revealed that CTS decreased the levels of TNF-α, IL-6 and TGF-β1 expressed in RAW 264.7 cells, and reduced α-SMA, collagen-Ⅰ, MMPs concentrations in HFL-1 cells co-cultured with the supernatant of RAW264.7 cells after hyperoxia. CTS can attenuate the hyperoxia-induced inflammatory response and the level of fibrosis by regulating the levels of inflammatory factors and fibrotic factor TGF-β1 expressed by macrophages, thereby highlighting the therapeutic potential of CTS in the treatment of BPD.